Dry-Dock Supervision Analysis of KM. L. Malahayati (Ship Owner: Poltekpel Malahayati Aceh) at PT. Cahaya Baru Shipyard - Harris R. Dahlan; Joshian Nicolas William Schadaw; Lucia I. R. Lefrandt; Semuel Palembangan (ALTAIR: Jurnal Transportasi dan Bahari, 2026)
The annual dry-dock supervision of KM. L. Malahayati is an important aspect in ensuring the quality, safety, and operational efficiency of the ship. This study aims to evaluate the effectiveness of dry-dock supervision with technical, administrative, and regulatory approaches. The research method employs a descriptive qualitative approach, based on field observations, documentation, and data validation through triangulation of shipyard reports and technician interviews. Quantitative analysis was conducted on time deviation, cost efficiency, and work safety indicators. The results show a 33% deviation in finishing time, but overall the project was completed on time with cost efficiency and increased work safety. This study contributes in the form of an integrated dry-dock supervision model that is relevant for government training vessels.